PEMIKIRAN DAN PENEMUAN ILMUWAN MUSLIM - Syaihul Hakim (LPPM Institut Agama Islam Al-Hikmah Tuban, 2013)
The Contribution of Muslim philosophers thinking is very influential on the development of philosophy, it is proved by the various works in the form of a book or books are used as reference in the study of philosophy in both the Middle East and in the regions of Europe. The works of Muslim scientists were widely translated into other languages for examples: Ibn Rushd (Averroes), Ibn Sina, Al-Kindi, and other Muslim philosophers.The findings Muslim scholars are very influential in the changing world of civilization, because the key findings from technology, chemistry, astronomy, mathematics, fashion, airplanes, coffee, soap, etc. was originally invented by Muslim scientists in the reign of Bani 'Abbasyyah power, which further developed by other scientists to date